(untitled) (Research, Society and Development, 2021)
Objective: Constructing and validating a checklist for indication of noninvasive ventilation in elderly after stroke. Method: A methodological study conducted from October to November 2017 in a general hospital in the State of Paraiba, Brazil. Two groups of participants were established, the first called GD (group of doctors and experts in respiratory physiotherapy) and the second GP (group of physiotherapists working in cardiorespiratory care with the old),and these groups were composed of 10 participants each. After issuing the opinions of the GD and GP participants, the checklist was prepared. Results: There is feasibility of clinical application of the checklist, and this can assist in decision making. Its relevance was demonstrated by statistical significance (p=0.007), with the possibility of application in a short time (p=0.0001); regarding the content coverage, 50% of the participants (n=10) reported that the checklist is comprehensive and 50% (n=10) stated that it is necessary to increase content; all participants were unanimous that the instrument has good presentation, is objective, coherent and clear in its content (n=20; 100%). Conclusion: The importance of the instrument in decision-making in the indication of noninvasive ventilation in elderly after stroke was observed. The checklist is a technological resource that contributes to this decision-making, makes professional practice easier and serves as a basis for new public policies, as it provides benefits to the health of the elderly, besides generating shorter hospitalization time and avoiding worsening in the situation of the elderly after stroke.